2016
DOI: 10.1007/s12035-016-9955-6
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic P2Y1 Receptors Control Rapid Expression of Plasma Membrane Processes in Hippocampal Astrocytes

Abstract: Astrocytes regulate neuronal activity and blood brain barrier through tiny plasma membrane branches or astrocytic processes (APs) making contact with synapses and brain vessels. Several transmitters released by astrocytes and exerting their action on several receptor classes expressed by astrocytes themselves influence their physiology. Here we found that APs are dynamically modulated by purines. In live imaging experiments carried out in rat hippocampal astrocytes, Gq-coupled P2Y1 receptor blockade with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Functionally, the P2Y1 receptor signaling pathway is one of the major purinergic signaling pathways that may contribute to altered astrocyte properties in neurodegeneration, especially in AD. P2Y1 mediates calcium waves in astrocytes, which are linked to gliotransmitter release and synchronization of astrocytic syncytium, which is critical for synaptic plasticity (149)(150)(151). Unlike in the transcriptomic studies we summarized here, previous studies showed that astrocytic P2Y1 receptor expression is elevated in AD mouse models and human AD brain, especially in close vicinity to amyloid plaques (151,152).…”
Section: Astrocytesmentioning
confidence: 63%
“…Functionally, the P2Y1 receptor signaling pathway is one of the major purinergic signaling pathways that may contribute to altered astrocyte properties in neurodegeneration, especially in AD. P2Y1 mediates calcium waves in astrocytes, which are linked to gliotransmitter release and synchronization of astrocytic syncytium, which is critical for synaptic plasticity (149)(150)(151). Unlike in the transcriptomic studies we summarized here, previous studies showed that astrocytic P2Y1 receptor expression is elevated in AD mouse models and human AD brain, especially in close vicinity to amyloid plaques (151,152).…”
Section: Astrocytesmentioning
confidence: 63%
“…Potassium buffering by inwardly rectifying K + (Kir) channels during neuronal activity is fundamental to maintain adequate synaptic transmission and neuronal excitability 24 . We have previously shown that Kir channels are functionally expressed in primary hippocampal astrocytes 25 . Therefore, we performed patch-clamp experiments in WT-iAstro#2 and 3Tg-iAstro#2 lines.…”
Section: Resultsmentioning
confidence: 99%
“…4D) and adenylyl cyclase-sensitive responses (SQ22536, Figure 4D) (Caruso et al, 2012) showed comparable ability to depress calcium waveform amplitudes by roughly half and equivalent statistical significance in limiting the generation of SE astrocytes (Table S1). The efficiency of U73122 in inhibition of the PLC pathway was verified using an inactive analogue in parallel experiments (U73343: Figure S3) (Chisari et al, 2017). The inhibition effect of U73122 lends further credence to the impact of PLC pathways on astrocyte responsiveness.…”
Section: Ll Open Access Isciencementioning
confidence: 68%